(untitled) (Research, Society and Development, 2023)
Recently, niobium-based oxides have attracted increasing interest as a potential choice for lithium-ion battery technology. The mixed oxide of niobium and titanium, in the composition of TiNb2O7, has been considered a promising candidate for the anodic materials of new generation lithium-ion batteries. However, its precursors require a severe and costly purification process since they are processed from complex ores. In addition to the purification cost, these steps result in significant amounts of acid and alkaline effluents, which generate additional costs for their treatment. The present research was designed to understand the influence of contaminants commonly found in ores or inserted in the process routes to obtain niobium oxides. Iron, potassium, phosphorus, tantalum, and fluoride were inserted into the TiNb2O7 synthesis process from ultrapure solutions. The mixed oxides obtained were subjected to characterizations by the X-ray diffraction technique, scanning electron microscopy and finally, applied to lithium-ion batteries to evaluate the influence on the electrochemical performance. The results showed that, despite the impact on the formation of the compound TiNb2O7, the presence of iron up to 2,000 ppm in the synthesis was not harmful to the process in general, while the presence of phosphorus and potassium resulted in serious problems in the electrode preparation steps. On the other hand, the presence of tantalum promoted important increases in battery performance, attributed to the formation of high purity mixed oxides (TiNb2O7 and TiTa2O7).